Hospital School Students' Academic Motivation and Support Needs: A Self-Determination Perspective - Mombaers, Tine; Donche, Vincent (Frontiers in Education, 2020)
In contrast with the phletora of studies on academic motivation of regular students in regular educational settings, this study aims to shed light on the motivational drive and 'educational support needs' of chronically ill children in hospital schools. This in-depth qualitative study wants to explore if the expected motivational dimensions central in SDT research are present among this specific population and setting and if the expected relationships with 'needs' are present. In contrast with research on academic motivation and needs in common classrooms, research in hospital schools is very scarce. Using the theoretical framework of self-determination theory, we investigated the presence of different types of motivation in relationship with ABC. More specifically, we investigated their motivational types which we then related to the needs they wanted their hospital school teacher(s) to fulfill. A purposive selected sample of six students with a chronic and/or long-term illness from three different hospital schools in Flanders (Belgium) was interviewed, using elicitation techniques to further deepen the data collection. Despite of their chronic illness, all participating students were academically motivated, though some students indicated that not feeling well could cause temporary motivational regression. We were able to distinguish differences in motivation type and preferable need support. More controlled motivated students from the university hospital schools indicated a preference for support in terms of relatedness. More autonomously motivated students from a hospital school within a revalidation centre showed more autonomous motivation and preferred competence support, instead of the autonomy-support that would be expected according to self-determination theory. Moreover, the educational context and the types of illnesses or treatments seem to be linked with students’ motivation types and preferred support.